2022
DOI: 10.1097/ta.0000000000003548
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tranexamic acid dosing regimen on trauma/hemorrhagic shock-related glycocalyx degradation and endothelial barrier permeability: An in vitro model

Abstract: BACKGROUND: Improved outcomes with early tranexamic acid (TXA) following trauma hemorrhagic shock (T/HS) may be related to its antifibrinolytic, as well as anti-inflammatory properties. Previous in vitro studies have shown that early TXA administration protects against T/HS endothelial barrier dysfunction and associated glycocalyx degradation. An intact endothelial glycocalyx may protect against subsequent neutrophil mediated tissue injury. We postulated that early TXA administration would mitigate against gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Advancements in trauma care increasingly recognize the importance of targeting the dynamic and complex nature of this host response to injury 4,34,35 . In in vitro and animal models of trauma, TXA has been shown to reduce glycocalyx degradation 20 and protect the endothelium 7,21 . Prehospital interventions impact the host response to injury and may specifically mitigate dysregulated endothelial and inflammatory processes 4,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in trauma care increasingly recognize the importance of targeting the dynamic and complex nature of this host response to injury 4,34,35 . In in vitro and animal models of trauma, TXA has been shown to reduce glycocalyx degradation 20 and protect the endothelium 7,21 . Prehospital interventions impact the host response to injury and may specifically mitigate dysregulated endothelial and inflammatory processes 4,32 …”
Section: Discussionmentioning
confidence: 99%
“…In vitro and animal experiments have shown that TXA reduces syndecan-1 shedding 18 and protects the endothelial glycocalyx 19,20 . Importantly, these results may be sensitive to the dose and timing of TXA administration 15,21 . Tranexamic acid has also been shown to have beneficial effects on vascular permeability, inflammation, and glycocalyx degradation beyond antifibronolysis, highlighting several gaps in our mechanistic understanding of this drug 7 …”
mentioning
confidence: 99%
“…Our earlier studies demonstrate that TXA at physiologically relevant concentrations reduce MMP and other cell related metalloproteinases in our in vitro microfluidic studies. 2 von Willebrand factor multimers secreted from activated endothelial cells may enter the circulation or remain anchored to the endothelial surface. P-selectin and dvβ3 integrins had been proposed as attachment points for vWF factors on the surface of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that tranexamic acid (TXA) protected the endothelial glycocalyx layer from degradation using a microfluidic model of the microcirculation subjected to hypoxia-reoxygenation (HR) and catecholamine excess. 2 We hypothesized that TXA administration following shock conditions would impact the vWF-ADAMTS-13 axis by protecting the glycocalyx from degradation. This was studied in an endothelial microfluidic flow study.…”
mentioning
confidence: 99%
See 1 more Smart Citation